2005
DOI: 10.1097/01.hjh.0000177536.53409.1a
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and body mass index in lean rural and semi-urban subjects in West Africa

Abstract: The relationship between BP and BMI is not linear, and is possibly sigmoid, but this may vary between subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
4
15
0
Order By: Relevance
“…Even so, the present correlation values were higher than those for age (0.05), BMI (0.088) and WC (0.061) reported by Onwubere et al [31] in another Nigerian traditional community of a different ethnicity with a prevalence of hypertension of 46.4% compared with 33.1% found in this study. This weak or lack of a relationship between body dimensions and BP has also been observed in other groups particularly within Africa [7,9,[29][30][31][36][37][38]. It should be noted that nearly two-thirds of individuals with elevated BP had a BMI of less than 25 kg/m 2 , thereby indicating that the dominant body type associated with hypertension in this group was lean.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Even so, the present correlation values were higher than those for age (0.05), BMI (0.088) and WC (0.061) reported by Onwubere et al [31] in another Nigerian traditional community of a different ethnicity with a prevalence of hypertension of 46.4% compared with 33.1% found in this study. This weak or lack of a relationship between body dimensions and BP has also been observed in other groups particularly within Africa [7,9,[29][30][31][36][37][38]. It should be noted that nearly two-thirds of individuals with elevated BP had a BMI of less than 25 kg/m 2 , thereby indicating that the dominant body type associated with hypertension in this group was lean.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, many individuals with elevated blood pressure (BP) are neither overweight nor obese. In some groups, the dominant body type associated with hypertension is lean [7][8][9]. These observations could raise the intriguing possibility that mechanism(s) beyond excess weight may be more important in driving an increase in BP, at least in some groups.…”
Section: Introductionmentioning
confidence: 99%
“…This is also well below US and European rates (Wolf-Maier et al 2003). Few data on blood pressure on population-based, non-clinical samples of older adults are available for Africa, although average blood pressure rates reported here are similar to those reported for younger samples in Tanzania (Unwin et al 2006) and Ghana (Kerry et al 2005). The prevalence of hypertension is lower in this sample compared to those reported in the samples above.…”
Section: Discussionsupporting
confidence: 53%
“…Kaufman et al (1997) showed there is a threshold effect at 21 kg/m 2 in women but not for men among the low-BMI populations in Africa and the The CPU time summarizes the average time (in seconds) used in computing the confidence interval for one data set Caribbean. In a study of lean rural and semi-urban in West Africa, Kerry et al (2005) showed that BMI has a nonlinear effect on diastolic BP with a significant "knot" point at BMI equal to 18 kg/m 2 for younger women. All these studies have focused on mean regression.…”
Section: Blood Pressure and Body Mass Index Analysismentioning
confidence: 99%